The Influence of Organizational Culture on Employee Performance - Nining Angraeni Ningsih; Haedar Akib; Muh Nasrullah (ASHA Publishing, 2024)
Workers will face difficulties in achieving company standards without the existence of a positive organizational culture. A strong organizational culture has a huge impact on performance, creating high motivation, a positive environment, creativity, and work-life balance. This not only improves performance, but also contributes to employee productivity and overall well-being. The purpose of this study is to assess the impact of organizational culture on employee performance. The method used is descriptive research with a quantitative approach. In order to achieve the objectives of this research, the data collection method is carried out through observation, questionnaire, and documentation activities. The research sample involved 66 people, with a sampling technique using the saturated sample method. The collected information was then evaluated by applying descriptive data analysis methods, validity and reliability tests, data normality tests, product moment correlation analysis, determinant coefficients, and simple linear regression analysis. The purpose of this analysis is to assess the impact of organizational culture on employee performance at the KMP LAN Makassar Center. The results showed that the overall organizational culture indicators were rated